Food safety issues and scientific advances related to animal-source foods - Makita, K.; Roesel, Kristina; Hung Nguyen-Viet; Bonfoh, Bassirou; Kang'ethe, Erastus K.; Lapar, Ma. Lucila; Grace, Delia (International Livestock Research Institute, 2014)
Every year, 2 billions of diarrhea cases occur for all age groups (WHO, 2010) and currently 700,000 children under five die from this illness (Walker et al., 2013). Animal-source foods provide nutrition but are a major cause of such food-borne diseases (FBDs). FBDs include other, non-diarrheal severe illness such as tuberculosis and brucellosis. In developing countries, most foods are sold through informal markets, which lack adequate hygiene management. However, these informal markets provide affordable food to the poor, and market opportunities to smallholder farmers and other value chain actors, and thus are economically important. Since 2008, the Safe food, Fair food project funded by GIZ, and run by International Livestock Research Institute (ILRI) proved that the concept of participatory risk analysis (Grace et al., 2008) is useful in improving food safety in informal markets while ensuring market access for smalholder farmers. In this risk analysis, participatory methods were applied to understanding the level of exposure to pathogens; cultural and traditional risk reduction behavior; communication with stakeholders of food safety; and, education of smallholder farmers and actors along food value chains. The project initially planned five proof-of-concept studies in five sub-Saharan African (SSA) countries, but expanded to 24 studies in eight SSA countries, attracting additional funds. Participatory risk analysis worked very well in quantifying risks and identifying better policy support options using stochastic modeling even in the data-scarce environment (Makita et al., 2012). The second phase in SSA started in 2012 with more emphasis on value-chain based risk analysis including risk management. The methodology was adopted in Asia- a study started in Vietnam on risk analysis associated with consumption of pork produced by smallholder farmers and vegetable, which is contaminated with pathogens of animal origin. Integration of economic analysis into food safety risk assessment along pork value chains is being applied in identifying incentive-based hygiene control options in this study. Also in Vietnam, a risk assessment taskforce was established to work jointly with the Ministry of Health and Agriculture on the use of risk assessment for food safety management. Participatory food safety risk analysis may improve hygiene of affordable food and at the same time livelihoods of actors along value chains of animal-source foods in Asia and Africa.